Asymptotical analysis of Cramer‘s transforms for extrema - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2021)
Asymptotic of normalized extrema of independent identically distributed random variables is analyzed. Normalization – Cramer‘s transforms [2].
Keywords: extremes; Cramer‘s transforms; rate of convergence